2013
DOI: 10.4103/0973-029x.119767
|View full text |Cite
|
Sign up to set email alerts
|

Central odontogenic fibroma of the maxilla

Abstract: The central odontogenic fibroma (COF) is a rare benign odontogenic mesenchymal tumor of jaw bones. The World Health Organization (WHO) recognizes two variants of COF namely: 1) Epithelial-rich type (WHO) and 2) epithelial-poor type (simple type). Rare variants like ossifying COF, COF associated with giant cell lesions, and amyloid have been documented. This article presents a case of an epithelial-rich variant of COF in a 24-year-old female. It presented as a bony swelling of the maxilla and appeared as a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 7 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…COF affect wide age ranged mainly between the 2nd and 4th decades of life. In 2005, Barnes et al found that COF has a female predilection [11]. On the other hand, Tkeoka reviewed eighteen Japanese cases from 1980-2010 found that COF affect both gender equally [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…COF affect wide age ranged mainly between the 2nd and 4th decades of life. In 2005, Barnes et al found that COF has a female predilection [11]. On the other hand, Tkeoka reviewed eighteen Japanese cases from 1980-2010 found that COF affect both gender equally [9].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelium-rich type-containing fibrous tissue in myxoid area associated with odontogenic epithelium and features of dysplastic dentine or cementum-like tissue [13]. The different histologically was attributed to the tissue of origin [11]. In a study done on dogs in 1983, it has been suggested that epithelium-poor type is derived from the dental follicle and the epithelium-rich type arises from the periodontal ligament [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHO variant is considered as a mesenchymal odontogenic tumor and is comprised of two distinct cell types, a fibrous element, and an epithelial component that resembles dental lamina or its remnants. In contrast, the non-WHO variant lacks an epithelial component and is said to be a monomorphic fibroblastic tumor, purported to be of odontogenic mesenchymal origin and ostensibly derived from pulpal or follicular fibroblasts [9]. …”
Section: Discussionmentioning
confidence: 99%